2021
DOI: 10.1002/imhj.21947
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ psychopathology symptoms and mindful parenting in the postpartum period: The role of parental reflective functioning

Abstract: Postpartum psychopathology has an adverse impact on parenting behaviors and, consequently, on the mother–infant relationship. This study aimed to explore whether the relationship between maternal anxiety and depression symptomatology in the postpartum period and the ability of mothers to adopt a mindful parenting approach is indirect and can be explained by parental reflective functioning. Two hundred ninety five Portuguese mothers of infants aged up to 12 months completed self‐report measures assessing anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…By contrast, in a similar community sample in which PRF was assessed at age 6 months using the PRFQ, Nobre‐Trinidade et al. (2021) reported that higher anxiety scores on the HADS related to lower certainty about mental states and higher pre‐mentalizing modes scores, with no association with interest and curiosity in mental states. Research on parental anxiety and PRF is lacking, as a recent systematic review highlighted (Risi et al., 2021), and it is therefore difficult to draw strong conclusions on the relation between these factors without further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, in a similar community sample in which PRF was assessed at age 6 months using the PRFQ, Nobre‐Trinidade et al. (2021) reported that higher anxiety scores on the HADS related to lower certainty about mental states and higher pre‐mentalizing modes scores, with no association with interest and curiosity in mental states. Research on parental anxiety and PRF is lacking, as a recent systematic review highlighted (Risi et al., 2021), and it is therefore difficult to draw strong conclusions on the relation between these factors without further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Depression in the postpartum period is highly prevalent, even amongst otherwise healthy mothers (Shorey et al., 2018). The condition has been linked with mentalizing impairments (Georg et al., 2023), negatively influencing the quality of the mother‐infant relationship (Krink et al 2018; Nobre‐Trindade et al., 2021). As the mother's capacity to hold the child's mind in mind throughout the moment‐to‐moment changes in the child's emotional state is considered crucial for sensitive caregiving (Slade, 2007), it is relevant to investigate if self‐reported mentalizing assessed in a non‐interactive, offline context relates to how the mother mentalizes upon the infant in an online context, and how this is expressed when the mother experiences depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…These relationships are complicated by the fact that many of these factors are associated with one another, such as the various forms of trauma-related psychopathology, as well as measures of alexithymia, socioeconomic status (SES), PRF, and maternal sensitivity [6,[11][12][13][14] which have multiple interrelations. The same is true for child outcomes: different factors show a complex pattern of univariate associations with each other.…”
Section: Introductionmentioning
confidence: 99%
“…PTSD resulting from childhood adversity associates also with symptoms of alexithymia (i.e., the difficulty in identifying and naming one's own and others' emotions, 9, 10). These relationships are complicated by the fact that many of these factors are associated with one another, such as the various forms of trauma-related psychopathology, as well as measures of alexithymia, socio-economic status (SES), parental reflective functioning (PRF) and maternal sensitivity (6,(11)(12)(13)(14) which have multiple interrelations. The same is true for child outcomes: different factors show a complex pattern of univariate associations with each other.…”
Section: Introductionmentioning
confidence: 99%